ШАВАРТЫН ХӨНДИЙ ОРЧМЫН МОРФОСТРҮКТҮҮР БА ДЕНУДАЦИ ХЭРЧИГДЛИЙН ГҮНИЙ АСУУДАЛД - Х.УЛАМБАДРАХ; Я.БОЛД (Geological Issues, 2023)
ШАВАРТЫН ХӨНДИЙ ОРЧМЫН МОРФОСТРҮКТҮҮР БА ДЕНУДАЦИ ХЭРЧИГДЛИЙН ГҮНИЙ АСУУДАЛД